Clinical Experience with a Medical Device Containing Xyloglucan, Hibiscus, and Propolis for the Control of Acute Uncomplicated Urinary Tract Infection-like Symptoms - Patricia Ortega; Esther Benito; Félix Berrocal (Uro, 2022)
Background: The development of drug resistance among causative agents has resulted in the need to change the paradigm toward alternative therapeutic approaches for uncomplicated urinary tract infections (UTIs). The objective of the present study was to evaluate the efficacy of an oral medical device containing xyloglucan, hibiscus, and propolis in clinical practice with a cohort of women from Switzerland with UTI-like symptoms and the administration of concomitant drugs. Materials and Methods: This work describes an observational, prospective, and multicenter study involving 103 women attending a primary care physician for a symptomatic episode, or recurrence, of acute uncomplicated cystitis between August 2018 and June 2019. Utipro®Plus was administered orally, with patients being prescribed two capsules per day for 5 days to control discomfort symptoms or one capsule per day for 15 consecutive days per month (followed by a 15-day break for a 3-month cycle) to prevent recurrences. Results: A total of 84 women (81.6%) did not require an additional consultation, whereas 17 (16.5%) required a second one. Inadequate treatment response was found in 7 women out of the 19 who required a further consultation (36.8%): 3 women with no history of cystitis (out of 13, 23.1%) and 4 with recurrent cystitis (out of 6, 66.7%). None of the women from the study reported an adverse event. Conclusions: The studied product containing xyloglucan, hibiscus, and propolis is safe and effective for the treatment of a broad spectrum of women with acute uncomplicated or recurrent UTI-like symptoms.